Endometrial Receptivity and Intrauterine Adhesive Disease - Evans-Hoeker, Emily A.; Young, Steven L. (Seminars in Reproductive Medicine, 2014)
Intrauterine adhesions (IUA) can occur after mechanical or infectious injury to the endometrium. Normal endometrial repair occurs without scar formation; however, in some women, these normal repair mechanisms are aberrant, resulting in IUA formation. The exact alteration in repair mechanisms is not well understood; however, it likely involves hypoxia, reduced neovascularization, and altered expression of adhesion-associated cytokines. The prevalence of IUA varies by the type of injury and ranges from 16 to 24% in women undergoing pregnancy-related curettage and 31 to 45% after hysteroscopic myomectomy. The presence of IUA may result in infertility and/or pregnancy complications; thus, hysteroscopic adhesiolysis is typically recommended before conception. Sharp dissection rather than cautery to resect adhesions and postoperative treatment with an IUA barrier and estrogen may decrease the likelihood of recurrence. Menstrual history before hysteroscopic repair and endometrial thickness after surgical repair may be useful in assessing endometrial receptivity and the likelihood of conception.
Keywords: intrauterine adhesion; Asherman syndrome; hysteroscopy; endometrial receptivity